Correlation Of Visceral Adiposity Index (Vai) & Hirsutism As A Predictor Of Metabolic Consequences In Poly Cystic Ovarian Syndrome (Journal of Pharmaceutical Negative Results, 2022)
Poly Cystic Ovarian Syndrome (PCOS) is one of the most common reproductive and metabolic disorders among women of reproductive age. Women suffering from PCOS present with an array of symptoms connected with menstrual dysfunction and androgen excess, which significantly impacts their health well being. PCOS women are likely to be at increased risk of multiple co-morbidities, including insulin resistance, obesity and cardiovascular disease (CVD), type II diabetes mellitus, infertility and psychological illness. The most commonly exhibited problems noticed in PCOS is menstrual cycle disturbances (oligo/amenorrhea), hirsutism, infertility, dyslipidemia and metabolic disturbances due to insulin resistance (IR). Obesity, in particular visceral obesity, is associated with an increased risk of metabolic diseases, such as cardiovascular disease, pre-diabetes and type 2 diabetes (dysglycemia), hypertension and dyslipidemia. Cardio-metabolic diseases are the global leading causes of death and represent a significant economic burden on health systems. The pressure to search for and use new effective preventive tools increases and given the current epidemiological situation, as these diseases are to a large extent preventable. This review is an attempt to correlate the visceral adiposity index (VAI) & hirsutism in predicting metabolic consequences in PCOS.